PENGARUH INSENTIF DALAM MENINGKATKAN KEDISIPLINAN PEGAWAI MELALUI INTERVENING KEPUASAN KERJA - Opiq Piqhi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Compliance is an important issue for employees in government agencies. This study aims to examine the effect of incentives on employee discipline through the intervening variable of job satisfaction. The object of research is civil servants at RSUD dr. Drajat Prawiranegara Serang with the number of samples taken as many as 125 people. Analysis of research data using the SEM-PLS method. The results showed that incentives had no effect on employee discipline. Incentives have a positive and significant effect on employee job satisfaction. Job satisfaction has a positive and significant effect on employee discipline. In this study, job satisfaction was proven to partially mediate the effect of incentives on employee discipline